STUDI ADMINISTRASI DALAM RANGKA REFORMASI BIROKRASI DI INDONESIA (ANALISIS PERBANDINGAN INDONESIA – JEPANG) - Drs. Riyadi, Drs. Riyadi (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2004)
Comparing the recent condition of bureaucracy between Indonesia Japan reveals a normative similarity, concerning the independency of civil service. This has just started in Indonesia since the beginning the reformation era in 1999, while in Japan such condition has long happened since 1970-ies. However, in terms of the institutional existence and management patterns, the implementation of such neutrality is rather difficult to realize since the top management of bureaucracy in general relies on the political official, namely the State Minister of Apparatus Management (Menpan). Rather, there should be an evaluation and reform towards the implementation of bureaucracy. In the institutional system, a centralized management might be more effective if carried out by an independent institution than four institutions (Menpan, LAN, BKN, and BPKP). Besides easing coordination, it will also impact on the cost and resource efficiency. The independence of civil service should also be realized, not only in the form of normative regulations but also in its implementation by considering the existing authoritative and institutional condition.